Socio-economic characteristics of lac growers in Jharkhand - Govind Pal; M.L. Bhagat; A. Bhattacharya (Journal of Agricultural Extension Management, 2025)
Lac cultivation plays an important role in the farmers’ economy in remote and under developed areas of Jharkhand, West Bengal, Chhattisgarh, Madhya Pradesh, Orissa, Maharashtra and parts of Uttar Pradesh, Andhra Pradesh, Gujarat and NEH region. The lac growing regions of these states are characterized by a high proportion of tribal population, families living below the poverty line and a low literacy rate. The per capita income in Jharkhand was very low (Rs. 4,161 .00) in comparison to that of the national average (Rs. 20,860.00) during 2003-04 (Anonymous, 2005). About 57 per cent of the population is below the poverty line in Jharkhand as against the national average of 26.1 per cent during 1999-2000 (Dutta and Sunderam, 2002). Around 23.22 lakh families in the rural areas of Jharkhand live below the poverty line, out of which 3.91 lakh belong to SCs and 8.79 lakh to STs. Poverty amongst the ST population is more pronounced and it is about 60.60 per cent against the national average of 44.45 per cent during 1999-2000. Jharkhand has one of the lowest rates of literacy in the country, which is only 54.13 per cent in 2001. The female literacy rate is still lower at 39.38 per cent. The literacy rate among tribals of Jharkhand is 46 per cent and tribal female literacy rate is 32 per cent (Sharan and Neelkanth, 2002).